Process evaluation of We Can Quit- stop-smoking programme for women in socio-disadvantage in Ireland. (20th October 2021) - Darker, C; Burke, E; Castello, S; O'Sullivan, K; Vance, J; Buggy, A; Loudon, K; Williams, P; Dobbie, F; Hayes, C
Abstract: Background: Smoking tobacco poses a serious risk of early preventable death and disease for women living with socioeconomic disadvantage (SED). A smoking cessation programme 'We Can Quit' (WCQ) tailored to women living in four SED areas developed in Ireland included group support delivered by trained lay local women and free nicotine replacement therapy (NRT). The intervention was pilot tested in a community-based, cluster randomised controlled trial, 'We Can Quit 2'. Results of an embedded process evaluation to assess feasibility and acceptability of the programme and trial processes are presented. Methods: The design was qualitative using the Medical Research Council's (MRC) process evaluation framework. Semi-structured interviews with trial participants (N = 18) and Community Facilitators (CFs) who delivered WCQ (N = 8) were conducted. An inductive approach was used and data were analysed using thematic coding. Results: Peer-modelling, a non-judgemental environment, and CFs supportive role were viewed as facilitative elements of group support. Potential for broader message diffusion into the social networks of participating women was observed. Participants reported that free access to NRT was helpful for cessation. Some participants expressed concerns about NRT side effects. Community pharmacists provided important guidance relating to NRT and additional support between group sessions. Provision of a saliva samples proved challenging. Low literacy was a barrier to engagement with the programme and completion of trial-related materials. Hypothetical scenarios of direct or indirect observational fidelity assessment for a definitive trial (DT) were acceptable. Conclusions: The MRC framework proved useful to capture the experience of women smokers in SED areas of engaging with a community-based smoking cessation trial. Programme and trial-related processes were feasible and acceptable. A future DT will need to address low literacy. Key messages: A group-based stop-smoking programme including free NRT was acceptable and feasible to programme deliverers and women smokers living in disadvantaged communities. Women's low literacy was a barrier to engagement with trial and completion of programme materials.